Factory eco-efficiency modelling: framework application and analysis - Davé, Aanand; Salonitis, Konstantinos; Ball, Peter D.; Adams, Mark; Morgan, David (Elsevier, 2016)
Eco-efficiency is becoming an increasingly important organisational performance measure. Currently manufacturers rely on reactive methods such as auditing for assessment. There are still significant theoretical and practical barriers including a lack of knowledge regarding data granularity, model results quality and split incentives between facilities and manufacturing asset management. The purpose of this paper is to show the application of an eco-efficiency modelling framework in the case of a furniture-manufacturing factory. The framework composes resource and production data. These are analysed with respect to three data granularity factors, asset subdivision, time-step, and resource magnitude. Modelling is used to represent asset eco-efficiency across available subdivisions using performance indicators. This paper contributes to industrial sustainability literature by applying a factory eco-efficiency modelling framework in a comparative study of the case company's cursory and detailed data. Facility, utility and manufacturing assets are modelled and analysed from logged data granularity factors.
Keywords: Factory; Eco-efficiency; Modelling; Data Granularity Framework; Data Composition; Simulation